Evaluation of high density polyethylene plastic bag performance towards edge and point stresses using taguchi method - Ng, Si Jin; Yong, Tze Mi (2021)
Plastic bag are widely used due to it is low cost and convenience for packaging items. The problem with the strength of the plastic bag tends to tear easily and perforated. This study aims to validate the simulation results of High Density Polyethylene (HDPE) plastic towards HDPE plastic bags manufactured in UTHM and thus to evaluate the performance of plastic bag towards mass, edge and point stresses. The tensile test simulation was conducted using Solidworks 2017 to validate the HDPE plastic material properties by comparing the tensile test performed according to ASTM D882-18. The real life application was conducted to validate the simulation result by comparing plastic film’s displacement with different mass applied. Taguchi Method was used to arrange the edge and point stress test parameter with varied angle, mass, length and distance between the loads. The result showed that the error percentage for all loads was lower than 10.00 % for simulation compared to experimental tensile test. It also showed that error percentage was less than 5.00 % by comparing real life application and simulation results for displacement of plastic film. For mass stress test, the loads with 5.0 kg square base has the highest stress acted on the plastic film’s surface which is 22.399 MPa. For edge stress test, sample D with 1.0 kg, 20 mm of edge’s length and 20 ° of edge’s angle have highest maximum stress and displacement acted on plastic film’s surface which are 34.086 MPa and 84.94 mm respectively. For point stress test, sample G with 1.0 kg, 10 ° of angle and 30 mm of the distance between the point load have highest maximum stress and displacement acted on surface of plastic film which are 50.676 MPa and 63.64 mm accordingly. Both sample D and G were perforated since the maximum stress acted was exceed the tensile strength of HDPE plastic which is 28.4 MPa. The validation of HDPE plastic towards HDPE plastic bag manufactured in UTHM was proven from the result obtained. The plastic bag’s performance towards mass, edge and point stresses was successfully evaluated by using Finite Element Analysis and Taguchi Method.